2019
DOI: 10.1109/led.2019.2943242
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of 200-, 100-, and 50-$\mu$ m Pitch Resistive AC-Coupled Silicon Detectors (RSD) With 100% Fill-Factor for 4D Particle Tracking

Abstract: We designed, produced, and tested RSD (Resistive AC-Coupled Silicon Detectors) devices, an evolution of the standard LGAD (Low-Gain Avalanche Diode) technology where a resistive n-type implant and a coupling dielectric layer have been implemented. The first feature works as a resistive sheet, freezing the multiplied charges, while the second one acts as a capacitive coupling for readout pads. We succeeded in the challenging goal of obtaining very fine pitch (50, 100, and 200 µm) while maintaining the signal wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…For what concerns the transient properties, unirradiated RSD1 have been tested in the Silicon Laboratory at Università degli Studi di Torino and in the SSD Lab at CERN (EP-DT Department). Both campaigns confirmed that we succeeded in the challenging goal of producing very-fine-pitch Silicon detectors with internal gain and 100% fill-factor [1]. As an example, the 2D maps of charges obtained with a TCT (Transient Current Technique) [11] setup, and shown in panels (a) and (b) of Figure 5, demonstrate that we have been able to design a correct readout scheme with an effective segmentation down to a nominal pitch of 50×50 µm 2 .…”
Section: Static/dynamic Detectors Characterizationsupporting
confidence: 66%
See 1 more Smart Citation
“…For what concerns the transient properties, unirradiated RSD1 have been tested in the Silicon Laboratory at Università degli Studi di Torino and in the SSD Lab at CERN (EP-DT Department). Both campaigns confirmed that we succeeded in the challenging goal of producing very-fine-pitch Silicon detectors with internal gain and 100% fill-factor [1]. As an example, the 2D maps of charges obtained with a TCT (Transient Current Technique) [11] setup, and shown in panels (a) and (b) of Figure 5, demonstrate that we have been able to design a correct readout scheme with an effective segmentation down to a nominal pitch of 50×50 µm 2 .…”
Section: Static/dynamic Detectors Characterizationsupporting
confidence: 66%
“…RSD (Resistive AC-Coupled Silicon Detectors), a new generation of particle trackers with internal gain [1], are specifically intended for high-luminosity environments in near-future HEP experiments, in which Silicon sensors is the enabling technology to perform 4D particle detection [2]. Contrarily to the standard segmented LGAD (Low-Gain Avalanche Diode) [3], where each active area is surrounded by proper isolation implants (see panel (a) of Figure 1) needed to avoid short-circuit and early breakdown at edges, RSD are based on a continuous gain layer.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, TCT measurements, where a pulsed laser stimulated the secondary charge production through impact ionization, have been extensively used to provide 2D maps of charges induced on the AC-pads [1]. From these studies it was possible to point out that: (i ) signals are bipolar (due to the capacitive nature of the RSD readout scheme), (ii ) the charge, in general, is always induced in more than one pad and (iii ) the amplitude of signals decreases when the laser moves away from a pad, while the peak shifts in time.…”
Section: Sensors Design and Characterizationmentioning
confidence: 99%

The second production of RSD (AC-LGAD) at FBK

Mandurrino,
Arcidiacono,
Bisht
et al. 2021
Preprint
Self Cite
“…LGADs with a resistive sheet under the electrodes, also allowing for a uniform gain layer [24]. The most prominent radiation effect in LGAD sensors is the drastic reduction of gain achievable in the device, and shift of the same gain to higher bias voltages with irradiation (Fig.4a).…”
Section: Pos(vertex2019)028mentioning
confidence: 99%